Hubungan Interaksi Kelompok terhadap Pencapaian Tujuan dan Perkembangan Karakter Okabe Rintarou dalam Anime Steins;Gate 0 - Aditya Permana; Ethel Deborah Lewerissa (Faculty of Letters, Dr. Soetomo University, 2022)
This study aims to prove the effectiveness of the interaction process in groups on goals achievement and character development in Anime Steins;Gate 0. This study used a descriptive qualitative method regarding the theory of interaction process analysis by Robert F. Bales. This study uses data on interpersonal communication between group members dialogues categorized according to interaction process analysis theory (positive socio-emotional area, neutral task, and negative socio-emotional area). The writer found that interaction and communication between group members in the story were carried out during problem-solving through discussion and exchanging ideas, opinions, assessments, suggestions, and input. Both aspects are shown through delivery and interpretation to become the fruit of thought that unites their perception of purpose. Interaction and communication affect character development and their success in solving problems they face. Keywords: interaction; character development; communication; Okabe Rintarou.